RELATIONSHIP BETWEEN NOISE AND BLOOD PRESSURE IN FINISH MILL WORKERS AT PT. SEMEN X - Evodius Brian Bastrianto; Denny Ardyanto; Endang Dwiyanti; Putri Ayuni Alayyannur; Theodolus Bastrianto Parmada Ekka (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
Workplace noise is one of the common environmental problems, especially in heavy industries such as cement. Loud noise produced by machines and heavy equipment often exceeds the established Threshold Limit Value (TLV). High noise exposure can cause hearing loss, stress, and other health problems. One of the possible impacts is changes in blood pressure, which can increase the risk of cardiovascular disease. This study aims to explore the relationship between noise generated at the Finish Mill and workers' blood pressure, as well as to identify preventive measures that can be implemented to protect workers' health and improve working conditions at PT. Semen X. The method used in this study was a cross-sectional study conducted at PT. Semen X in July 2024. Based on the chi-square test, age, length of service, length of exposure, use of PPE, and medical history showed that workers' normal blood pressure was more common before work, while after work their blood pressure tended to increase. The conclusion of this study shows that the intensity of noise in the finish mill section is quite high and health disorders in blood pressure in workers show signs of hypertension or abnormal blood pressure fluctuations.